2008
DOI: 10.1016/j.envres.2007.09.008
|View full text |Cite
|
Sign up to set email alerts
|

No effect of cigarette smoking dose on oxidized plasma proteins

Abstract: Cigarette smoking is a major source of oxidative stress. Protein carbonyls have been used as a biomarker of oxidative stress because of the relative stability of carbonylated proteins and the high protein concentration in blood. Increased levels of carbonyl groups have been found in serum proteins of smokers compared to nonsmokers. However, neither the dose effect of current cigarette smoke nor other predictors of oxidative stress have been studied. Hence, we used an Enzyme-Linked Immunosorbent Assay (ELISA) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 37 publications
0
32
0
1
Order By: Relevance
“…The Western blot study also examined differences in oxidized serum proteins between heavy and light smokers and found none. We also found no association of protein carbonyl content with cumulative or current smoking dose in the EMCAP study, although associations were found with age, ethnicity, educational attainment and obesity in this cohort (Yeh et al 2008), in agreement with prior studies (Baynes 1991, Giugliano et al 1996. Several studies have shown that protein carbonylation increases with the age of cells, organelles and tissues of varied species and has been associated to an exponential increase in molecular oxidative damage due to senescence of cells which leads to an imbalance with antioxidant mechanisms that occurs with age (reviewed by Chakravati & Chakravati 2007).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The Western blot study also examined differences in oxidized serum proteins between heavy and light smokers and found none. We also found no association of protein carbonyl content with cumulative or current smoking dose in the EMCAP study, although associations were found with age, ethnicity, educational attainment and obesity in this cohort (Yeh et al 2008), in agreement with prior studies (Baynes 1991, Giugliano et al 1996. Several studies have shown that protein carbonylation increases with the age of cells, organelles and tissues of varied species and has been associated to an exponential increase in molecular oxidative damage due to senescence of cells which leads to an imbalance with antioxidant mechanisms that occurs with age (reviewed by Chakravati & Chakravati 2007).…”
Section: Discussionmentioning
confidence: 77%
“…Protein carbonyls were measured on specimens stored for several years at −70°C. Stadtman and Levine (2003) have demonstrated the stability of protein carbonyls in storage for 10 years at −80°C and we have previously demonstrated expected associations in this cohort (Yeh et al 2008). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…: +91-8554-255761; Fax: +91-8554-255244; E-mail: vdp 1975@yahoo.co.in radicals and volatile aldehydes which are probably the major causes of damage to biomolecules. 4) The highly unstable free radicals attack important cellular constituents including DNA, proteins and other opportune targets, particularly cell membranes and the oxidative stress generated is implicated in the pathogenesis. 5,6) Electrolytes and minerals are involved as catalysts in most cellular enzyme catalyzed reactions and assume a major role in metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of death in the smokers measured by the number of cigarettes smoked daily, the duration of smoking, the degree of inhalation and the age of initiation 3,4 . Cigarette smoke contains over 4000 different chemicals, 400 of which are proven to be carcinogenic; it also contains various oxidants such as oxygen free radicals and volatile aldehydes which are probably the major causes of damage to biomolecules 5 . Cigarette smoking yields chemical substances with high cytotoxic potentials 6 .…”
Section: Introductionmentioning
confidence: 99%